A multifunctional carbon-base phase change composite inspired by "fruit growth". (5th March 2023) - He, Hongfei; Dong, Mingyang; Wang, Qingqing; Zhang, Jin; Feng, Quan; Wei, Qufu; Cai, Yibing
Abstract: Inspired by fruit growth, we proposed a strategy for the preparation of multifunctional phase change materials (PCMs) based on carbon-based porous materials. The composite was fabricated by using polymerization reaction of resorcinol-formaldehyde resin ("pulp") on the surface of three-dimensional skeleton of loofah sponge ("kernel") to form porous foam via high temperature carbonization, followed by further vacuum adsorption of paraffin wax ("fruit juice"). With excellent electrical and thermal conductivity, light absorption performance as well as thermal energy storage capacity, the designed phase change composite (PCC) system demonstrated superior performance in temperature management, photo/electrical thermal conversion, multi-driver thermoelectric generation and electromagnetic interference (EMI) shielding. The graded porous structure of carbon foam allowed for high adsorption capacity (∼91%) of paraffin wax which was leak proof, ensuring high enthalpy of the fabricated PCC. Enhanced thermal/electrical conductivity allowed the as-prepared PCCs to provide multi-source driven thermal management performance and excellent EMI shielding (∼52 dB). In addition, the prepared multifunctional PCCs exhibited high photothermal conversion efficiency (∼84%) and enhanced efficiency for thermoelectric generation. In summary, this study provided a novel route for the preparation of multifunctional PCCs and provided broad application prospects in advanced thermal management, energy conversion EMI shielding for PCMs. Graphical abstract: A novel graded porous carbon foam fabricated by growing on the surface of loofah fiber using synthetic growth agent, and phase change composites based the carbon scaffold demonstrated superior performance in temperature management, photo/electrical thermal conversion, multi-driver thermoelectric generation and electromagnetic interference (EMI) shielding. Image 1 Highlights: A new type of carbon scaffold for phase change materials was fabricated. The porous structure allowed for high capacity adsorption of PW and leak proof. The designed PCC system was multi-source (sunlight/electric/thermal) driven. The designed PCC system demonstrated superior multifunction.